Grammar- Translation Method vs. Role-Playing Teaching: A study of Effects on College Students’ Positive Attitudes Toward English Learning (مجلة ديالى للبحوث الانسانية, 2022)
Grammar- Translation Method vs. Role-Playing Teaching: A study of Effects on College Students’ Positive Attitudes Toward English Learning           Many researchers devote themselves to teaching materials that make students more interested in English class, while students’ positive attitudes in English classroom where different approaches are applied to teach the same materials are ignored most of the time. This research, therefore, is to investigate the relationship between such teaching methods as the grammar-translation method and role-playing teaching activity as a technique of communicative approach, of students’ positive attitudes toward English learning on the basis of 50 students at the department of English College of Education Al-Asmaee as subjects.        The findings indicate that in English classrooms the grammar translation method and role-playing teaching separately affect College students’ positive attitudes significantly with regard to the interest in English, expectation of attending English class, courage to speak English. Learners’ positive attitudes, which are based on their interests in English, their expectations of attending English class, their courage to speak English are defined as their feelings of English learning regarding achievement motivation and evaluated through comparing the  two methods. When learners are taught in classrooms with role-playing teaching and the grammar-translation approach alternatively for the purpose of exploring the differences of learners’ motivation increasing when a teaching material is taught in classrooms with quite different teaching approaches to prove that role-playing teaching does a much better job in increasing  learners’ motivation than the grammar-translation method and other questions related to students’ positive attitudes toward English class.